Canva and Quizizz Foster Algebraic Thinking in Junior High Students - Fajriah Fajriah; Husni Rahmah; Novianti Novianti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid advancement of digital technology has transformed educational practices, requiring teachers to integrate innovative media that enhance learning quality. Specific Background: In mathematics education, particularly algebra, students often struggle to understand abstract concepts due to conventional teaching methods. Knowledge Gap: Few empirical studies have examined the combined use of interactive media such as Canva and Quizizz to improve algebraic thinking in junior high school students, especially within limited-resource contexts like Bireuen. Aims: This study investigates the effectiveness of Canva and Quizizz interactive media in enhancing students’ algebraic thinking skills. Results: Employing a quasi-experimental design with pre-test and post-test control groups, findings show a significant improvement in the experimental group’s performance (Asymp. Sig (2-tailed) = 0.000 < 0.05), with an N-Gain of 0.7968 (high category), compared to 0.1456 (low) in the control group. Students expressed positive responses, indicating increased motivation and engagement. Novelty: The integration of Canva’s visual-based learning and Quizizz’s gamified assessment creates a synergistic model that bridges conceptual understanding and learner motivation. Implications: The study demonstrates that digital interactive media can effectively enhance cognitive and affective learning outcomes, offering a replicable framework for innovative mathematics instruction in the digital era. Highlights: Integration of Canva and Quizizz enhances students’ algebraic thinking. Interactive media improve motivation and engagement in learning. Visual and gamified approaches make abstract math concepts concrete. Keywords: Canva, Quizizz, Algebraic Thinking, Interactive Learning, Mathematics Education